Dendroid colleters on vegetative and reproductive apices in Alibertia sessilis (Rubiaceae) differ in ultrastructure and secretion - Machado, Silvia Rodrigues [UNESP]; Barreiro, Daniela Pacheco [UNESP]; Rocha, Joecildo Francisco; Rodrigues, Tatiane Maria [UNESP] (Elsevier Gmbh, Urban & Fischer Verlag, 2012)
In this work we compare the structure and secretion of dendroid colleters on stipules, bracts and sepals of Alibertia sessilis, a non-nodulate Rubiaceae species from Brazilian cerrado, with notes on the plant phenology. Samples were processed according to usual methods for anatomy, histochemistry and ultrastructure. Colleters are conical and constituted by a central axis of elongated parenchyma cells from which radiate numerous epidermal cells. Epidermal cells are cylindrical on the vegetative apex and digitiform or bulbous on reproductive apex. Both colleters produce hydrophilic and lipophilic compounds. on the vegetative apex, epidermal cells present numerous well-developed Golgi bodies associated with a network of smooth endoplasmatic reticulum (SER), scarce oil bodies and profiles of rough endoplasmatic reticulum (RER), indicating the involvement of these glands in the production of mainly polysaccharides in addition to protein and lipids. Differently, epidermal cells on bracts and sepals present abundant and prominent oil drops, fewer Golgi bodies and a well developed network of SER with locally dilated cisterns indicating predominance of lipids. Ecrine and granulocrine mechanisms are common to colleters of both apices. We hypothesize that exudates protect vegetative meristems and developing organs against desiccation in the dry season and against insects and pathogens during the wet season. Predominantly lipidic secretion protects the floral organs against dehydration in the dry season and can attract floral visitants. These aspects are relevant if one considers that A. sessilis inhabits the cerrado, an environment characterized by a well-delimited dry season, high irradiance and elevated vapor pressure deficits. (C) 2012 Elsevier GmbH. All rights reserved.
Keywords: Alibertia; Bracts; Dendroid colleters; Sepals; Stipules; Ultrastructure